Evaluation of strength parameters and structure analysis of an EN AW - 7075 aluminium alloy ring made by forging and rolling and heat-treated - J. Lulkiewicz; M. Gąsiorkiewicz; A. Kawałek; S. Szkudelski; T. Bajor; M. Chruściński; M. Bączek; B. Pachutko (Metalurgija, 2024)
The article presents the results of research on the evaluation of the structure and mechanical properties of a largesize ring made of aluminum alloy EN AW - 7075 according to a new technology, developed under the project “Innovative low-waste technology for forming large-size rings” carried out by Zarmen FPA forge with participation and support of the Lukasiewicz Research Network - Poznan Institute of Technology. Based on the tests, it was found that the produced ring was characterized by a homogeneous structure and the strength properties required by the customers.